Treatment of Heart Failure With Mid-Range Ejection Fraction: A Summary of Current Evidence - Ma, Teng; Su, Yang; Song, Jing; Xu, Dachun (Frontiers in Cardiovascular Medicine, 2021)
Heart failure (HF) is a complex syndrome causing heavy burden in public health, and the modern objective assessment of it is based on the left ventricular ejection fraction (LVEF). In 2016, the European Society of Cardiology classified the “gray area” in HF with LVEF of 40–49% as a new HF phenotype (HFmrEF) in an attempt to uncover the specific characteristics and treatment of these patients, which might recover or worsen to HFpEF or HFrEF, respectively, or conversely from these two subtypes. Up to now, many studies have demonstrated that patients with HFmrEF would possibly gain more benefits from some targeted therapies with HFrEF than those with HFpEF. This review summarizes what is known about the findings in the treatment of HFmrEF and discusses what should be done to better define the peculiar HF phenotype in the future.